EFEKTIFITAS SOFTWARE DAN APLIKASI SYUMILA NU 1.0 UNTUK PENGUATAN IDEOLOGI PESANTREN AN-NUR AL-HUDA DARI ANCAMAN PAHAM ISLAM TRANSNASIONAL - Wahid, Abdul; Marizakertaningtyas, Marizakertaningtyas (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2018)
This article discusses the results of research on the utilization of information technology, that isSyumila NU 1.0 software and application for reinforcement of students ideology in islamicboarding school An-Nur Al-Huda Ngawonggo Tajinan Malang. This application contained somebooks of pesantren curriculum, such as hadith, hahwu, sorrof/morfology, aqidah, fiqh, sufism etc.This application contains greatly facilitated, because around 60 % of books in this software hastranslated to Indonesian. As Tafsir Al-Jalalain has already been translated, which has an Arabictext. The most phenomenal advantage is this application is equipped with books that refutetransnational Islamic doctrines. This software and applications makes students and researchers ofIslamic studies easy, fastly, and effective in accessing islamic clasic references with modernmethode, especially to rebuttal of transnational Islamic ideologies. Thus, the development andutilization of information and communication technology in pesantren education can be moreadvanced, specifically in counteracting the dangers of transnational Islamic ideologies andeffective to counter it.Keywords: Effectiveness, Syumila NU 1.0, Idelogy, Islam, Transnational, Pesantren.